Carnitines as Mitochondrial Modulators of Oocyte and Embryo Bioenergetics - Martina Placidi; Giovanna Di Emidio; Ashraf Virmani; Angela D'Alfonso; Paolo Giovanni Artini; Anna Maria D'Alessandro; Carla Tatone (MDPI AG, 2022)
Recently, the importance of bioenergetics in the reproductive process has emerged. For its energetic demand, the oocyte relies on numerous mitochondria, whose activity increases during embryo development under a fine regulation to limit ROS production. Healthy oocyte mitochondria require a balance of pyruvate and fatty acid oxidation. Transport of activated fatty acids into mitochondria requires carnitine. In this regard, the interest in the role of carnitines as mitochondrial modulators in oocyte and embryos is increasing. Carnitine pool includes the un-esterified l-carnitine (LC) and carnitine esters, such as acetyl-l-carnitine (ALC) and propionyl-l-carnitine (PLC). In this review, carnitine medium supplementation for counteracting energetic and redox unbalance during in vitro culture and cryopreservation is reported. Although most studies have focused on LC, there is new evidence that the addition of ALC and/or PLC may boost LC effects. Pathways activated by carnitines include antiapoptotic, antiglycative, antioxidant, and antiinflammatory signaling. Nevertheless, the potential of carnitine to improve energetic metabolism and oocyte and embryo competence remains poorly investigated. The importance of carnitine as a mitochondrial modulator may suggest that this molecule may exert a beneficial role in ovarian disfunctions associated with metabolic and mitochondrial alterations, including PCOS and reproductive aging.